Genre filem biografi: Kajian ke atas filem-filem Malaysia kontemporari / Norfariza Subri - Subri, Nor Fariza (2006)
This research is conducted built on the motive to analyses biography-genre films in Malaysia especially on Leftenan Adnan directed by Aziz M. Osman. The other film is Raja Melewar which is being directed by Dato' Jamil Sulong. This research is geared towards in finding out the lack of genres in Malaysia and also questions to the production and debates on these issues. The writer chose this title or issues because to study more on biography history, biography films and also the elements from dramas and epics. In this research, the writer wants to see these elements both the films that are Leftenan Adnan and Raja Melewar. The method used is analysis content and data Collections.